2015
DOI: 10.1002/ejoc.201501306
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Acid Phosphatases in the Synthesis of Phosphorylated Monoalcohols and Diols

Abstract: A set of phosphatases was evaluated for their potential to catalyze the regio‐ and stereoselective phosphorylation of alcohols using a high‐energy inorganic phosphate donor, such as di‐, tri‐ and polyphosphate. Parameters such as type and amount of phosphate donor and pH of the reaction were investigated in order to minimize the thermodynamically favored hydrolysis of the phosphate donor and the formed phosphate ester. Diols were monophosphorylated with high selectivities. This biocatalytic phosphorylation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…All enzymes were tested with a broad range of substrates (Fig. ) including variously substituted primary ( 1a–11a ) as well as secondary alcohols ( 12a–16a ) in the transphosphorylation mode under standard reaction conditions (Tasnádi et al, ). Substrates bearing a sec ‐OH moiety ( 12a–16a ) were not accepted by PhoC‐Mm G92D/I171T and NSAP‐Eb 11‐mutants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All enzymes were tested with a broad range of substrates (Fig. ) including variously substituted primary ( 1a–11a ) as well as secondary alcohols ( 12a–16a ) in the transphosphorylation mode under standard reaction conditions (Tasnádi et al, ). Substrates bearing a sec ‐OH moiety ( 12a–16a ) were not accepted by PhoC‐Mm G92D/I171T and NSAP‐Eb 11‐mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Disodium α‐glycerophosphate hydrate ( 3b ) was purchased from TCI. 4‐Hydroxybutyl phosphate barium salt ( 1b ) and 2‐(acryloyloxy)ethyl phosphate barium salt ( 2b ) were prepared according to a literature procedure (Tasnádi et al, ,), racemic 2‐hydroxypropyl phosphate ( 6b ) was synthetized as reported (Lampson and Lardy, ). Ni‐NTA column for His‐tag purification was from GE Healthcare Life Sciences, Strep ‐Tactin Superflow High Capacity column for Strep‐tag purification was from IBA Solutions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations